The Influence of Employee Recruitment System and Performance on Increasing Employee Productivity Banyorang Coffee Processing Center Tompobulu District, Bantaeng Regency - Sri Mudefi; Zainal Ruma; Abdi Akbar; Siti Hasbiah; Agung Widhi Kurniawan (Economics and Business Journal (ECBIS), 2023)
This study aims to (1) determine the recruitment system has a partial effect on increasing employee productivity at the Banyorang coffee processing center, Tompobulu sub-district, Bantaeng district. (2) Knowing that employee performance has a partial effect on increasing employee productivity at the banyorang coffee processing center, Tompobulu sub-district, Bantaeng regency. (3) Knowing the recruitment system and employee performance simultaneously influence the increase in employee productivity at the Banyorang coffee processing center, Tompobulu sub-district, Bantaeng regency. This research was conducted at the Banyorang coffee processing center, Tompobulu sub-district, Bantaeng district. The data used in this study are primary and secondary data, with a total sample of 30 people. The results of the research hypothesis show that the recruitment system has a partial effect on employee productivity at the Banyorang Coffee Processing Center, Tompobulu District, Bantaeng Regency. This result means that with a good recruitment system, there will be an increase in Employee Productivity. The results of the research hypothesis show that employee performance has a partial effect on employee productivity at the Banyorang Coffee Processing Center, Tompobulu District, Bantaeng Regency. This result means that with good performance, there will be an increase in Employee Productivity. The results of the research hypothesis show that the recruitment system and employee performance simultaneously influence employee productivity at the Banyorang Coffee Processing Center, Tompobulu District, Bantaeng Regency.